Sociocultural pressures and adolescent eating in the absence of hunger - Reina, Samantha A. (2013)
Parental feeding practices and sociocultural pressures theoretically influence eating behavior. Yet, whether these factors relate to eating in the absence of hunger (EAH) is unknown. We assessed if sociocultural pressures were associated with EAH among 90 adolescents (M(age) = 15.27, SD = 1.39; 48% female). Parents completed the Child Feeding Questionnaire. Adolescents completed the Perceived Sociocultural Pressures Scale, Sociocultural Attitudes Towards Appearance Questionnaire-3, and Multidimensional Body Self-Relations Questionnaire-Appearance Scales. On two occasions, EAH was assessed as snack food intake after adolescents ate to satiety. Controlling for body composition and demographics, parental restriction and family pressure to be thin were associated with greater EAH. Media pressure was related to more EAH in girls. Appearance orientation and preoccupation with becoming overweight mediated links between sociocultural pressures and EAH. Findings support the notion that sociocultural pressures and their links to body image may contribute to the course of disinhibited eating behaviors during adolescence.